PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 001 BANTAYAN - Kasandra, Amjoni Kasandra Amjoni; Antosa, Zairul Antosa Zairu; ', Syahrifuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack : Problem on this research was that student’s  achievement on social studies at grade four of SDN 001 Bantayan was still low. Student’s who completed 7 student’s (35%) and did not completed 13 studen’ts (65%)  with mean score of 70. This research was done to implement the Cooperative Learning type Make a Match. It was aimed at improving student’s achievement on Social Studies at the Four Graderes of SDN 001 Bantayan by using the Make a Match type . These results indicate that the first cycle replicates individual student mastery increased from a base score that is 8 people who completed (26.66%) increased by 13 to 20 students (82.95%). In the second cycle increases by 3 people (11.9%) from the first cycle to 39 students (92.85%). In the third cycle increases by 4 people (7.15%) of the cycles of the second cycle to 20 students (100%). In conclusion, the implementation of Cooperative Learning type Make a Match was able to Improve Student’s achievement on Social Studies at the Four Graderes of SDN 001 Bantayan. Keyword:  Make a Match, the results of social studies